2015
DOI: 10.1590/1983-21252015v28n409rc
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade E Qualidade De Tubérculos De Batata Em Função Do Fertilizante Organomineral E Safras De Plantio

Abstract: RESUMO: O objetivo deste estudo foi avaliar a produtividade e a qualidade dos tubérculos da batateira em função da redução das doses do fertilizante organomineral em diferentes safras de plantio. Os experimentos foram conduzidos em Cristalina-Goiás nas safras de inverno (2013) e das águas (2013/2014). O delineamento experimental foi em blocos ao acaso, com 6 doses e 4 repetições na safra de inverno, totalizando 24 parcelas. Na safra das águas o experimento constituiu de 7 doses e 4 repetições, totalizando 28 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The association between organic acids and nutrients was favorable to the productivity of the class with the highest commercial value and total productivity. The results of the application of OMF to the productivity of several species have been reported in the literature (Ferreira et al, 2022;, including potato cultivation with pelleted OMF (Cardoso et al, 2015) and liquid OMF (Souza et al, 2017). Cardoso et al (2017) applied pelleted OMF in planting and observed a 22% higher productivity than mineral fertilizer, which corroborates the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The association between organic acids and nutrients was favorable to the productivity of the class with the highest commercial value and total productivity. The results of the application of OMF to the productivity of several species have been reported in the literature (Ferreira et al, 2022;, including potato cultivation with pelleted OMF (Cardoso et al, 2015) and liquid OMF (Souza et al, 2017). Cardoso et al (2017) applied pelleted OMF in planting and observed a 22% higher productivity than mineral fertilizer, which corroborates the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Studies demonstrate the organomineral as a promising alternative for the cultivation of garlic (Oliveira et al, 2021), sugar cane (Crusciol et al, 2020), potatoes (Cardoso;Lana, 2015) and corn (Sá et al, 2017). The use of fertilizer applied in the right dose, time, place and season contributes to good economic, environmental and social results (Casarin;STIPP, 2013).…”
Section: )mentioning
confidence: 99%
“…It is noteworthy that even in soils with high fertility, the use of organominerals can be advantageous by establishing a residual effect for future crops (Corrêa, 2018;Cardoso et al, 2015), releasing phosphorus for several years after application in the field (Antille, Sakrabani;Godwin, 2014).…”
Section: Onion Developmentmentioning
confidence: 99%
“…Due to environmental awareness and changes in legislation in recent years, coupled with the scarcity of raw materials to produce mineral fertilizers and the high costs for their production, the use of urban, industrial and agricultural waste in fertilizer formulation has been intensified in order to clean up the environment and create alternative products for use in agriculture. Cardoso et al (2015) reported higher productivity and better quality of tubers due to the use of organomineral fertilizers at the same levels of compost with mineral fertilizers. These fertilizers have been improved for use in different crops such as onion (Higashikawa and Menezes Júnior 2017), soy (Domingos et al 2018), sesame (Souza et al 2018), sweet potato (Polastreli et al 2018) and many other species, including cereals of great economic importance.…”
Section: Growth and Productivity Of áGata Potato Cultivar Under Diffe...mentioning
confidence: 99%